Mothers' Experiences of Having Children with Autism in A Special School (SLB) Negeri Jepara - Sri Hindriyastuti (International Forum of Researchers and Lecturers, 2022)
Background: Autism or ASD (Autism Spectrum Disorder) is a range of conditions characterized by some degree of impaired social behavior, communication and language, and a narrow range of interests and activities that are unique to the individual and performed repetitively. The majority of the phenomenon of maternal stress is higher than paternal stress. The purpose of this study was to explore more deeply the experiences of mothers who have children with autism in SLB Negeri Jepara. Methods: This study used a qualitative method with a phenomenological approach. The informants of this study are mothers who have children with autism. The selection of informants was carried out using purposive sampling technique (nonprobability sampling). The data collection technique used is in-depth interviews and data collection tools used such as interview guideline formats, notebooks, pens and other supporting tools such as cellphones as recording devices during interviews. Results: The results of this study are in accordance with the themes that the researcher has identified. According to the participants, it was not easy to immediately accept the child's condition when diagnosed with autism, so they experienced a variety of feelings, participants also made efforts to seek treatment for the child, during the process of caring for the child, participants said that the child had special care and some received social support. Conclusion: In this study it can be seen that there are four corresponding themes in the results. However, the four themes are less varied, so further research needs to be done on the experiences of mothers who have children with autism by developing these themes. autism